Hyperpolarized 129Xe Magnetic Resonance Imaging Sensor for H2S. Issue 32 (21st March 2017) - Yang, Shengjun; Yuan, Yaping; Jiang, Weiping; Ren, Lili; Deng, He; Bouchard, Louis S.; Zhou, Xin; Liu, Maili
Abstract: A new magnetic resonance imaging (MRI) molecular sensor for hydrogen sulfide detection and imaging using the nuclear spin resonance of hyperpolarized 129 Xe is developed. The designed MRI sensor employs cryptophane for NMR sensing, together with an azide group serving as a reaction site. It demonstrates a "proof‐of‐concept" that a fluorescent H2 S probe can be linked to a xenon‐binding cryptophane and thereby converted into an MRI probe, which could provide a very generalizable template. Abstract : Spinning around xenon : A new magnetic resonance sensor was constructed for H2 S imaging utilizing hyperpolarized 129 Xe nuclear spin resonance, which provides a generalizable template for the conversion of fluorescence sensor to a magnetic resonance imaging sensor.